2018 IEEE High Performance Extreme Computing Conference (HPEC) 2018
DOI: 10.1109/hpec.2018.8547782
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Launch of 16,000 Microsoft Windows Instances on a Supercomputer

Abstract: Simulation, machine learning, and data analysis require a wide range of software which can be dependent upon specific operating systems, such as Microsoft Windows. Running this software interactively on massively parallel supercomputers can present many challenges. Traditional methods of scaling Microsoft Windows applications to run on thousands of processors have typically relied on heavyweight virtual machines that can be inefficient and slow to launch on modern manycore processors. This paper describes a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…• Operating System Translators allow the execution of applications built for OSs different from the system host, e.g., WINE (Jones et al, 2018;Wine, 2022), WABI (Oracle, 2018), Lxrun (2022), Visual MainWin (Fisher et al, 2006), and Vcuda (Balis et al, 2021;S. Lin et al, 2009).…”
Section: • Multitasking Os Is Divided Into Operating Systemmentioning
confidence: 99%
“…• Operating System Translators allow the execution of applications built for OSs different from the system host, e.g., WINE (Jones et al, 2018;Wine, 2022), WABI (Oracle, 2018), Lxrun (2022), Visual MainWin (Fisher et al, 2006), and Vcuda (Balis et al, 2021;S. Lin et al, 2009).…”
Section: • Multitasking Os Is Divided Into Operating Systemmentioning
confidence: 99%
“…In fact, one of us reported that it is common for a large cloud to be managing 10 8 Spark tasks at a time [7]. Interactive parallel computing systems require launching thousands of jobs in a few seconds [21,32]. Obviously, one needs "gang" scheduling and straggler mitigation support.…”
Section: Introductionmentioning
confidence: 99%